HUBUNGAN ASUPAN LEMAK DENGAN KADAR HS-CRP SERUM PADA MAHASISWA OBES DAN TIDAK OBES DI FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI MANADO - Aprilianti, Fajar; Kawengian, Shirley E.S.; Bolang, Alexander S. L. (Universitas Sam Ratulangi, 2013)
Abstract: Fat consumption is now a growing thing in the notice due to changes lifestyle. Excessive fat will increase the risk of obesity and accounted for heart disease. Fat is the most dense source of energy, which produces 9 kcal / gram with the the total dietary fat consumption which is good for health should be 20-30% of the total energy needs. High sensitive C-reactive protein (hs CRP) is a very sensitive test for the detection of cardiovascular risk, coronary heart disease (CHD). The objective of this study was to examine the association between dietary fat intake and levels of hs CRP among the medical students of the Faculty of Medicine, University of Sam Ratulangi Manado. This study was an analytical cross-sectional design, conducted in November - December 2012 with 59 respondents. Using the Mann Whitney test, the result showed that there was no difference in dietary fat intake of obes and non-obes (p = 0.85 > 0.05 with z = -0,19). Levels of hs-CRP serum obes and non-obes showed that there was difference (p = 0.00 < 0.05 with z= -3,55). Spearman rank test, the result showed that there was no significant association between dietary fat intake and levels of hs-CRP among the medical students of the Faculty of Medicine, University of Sam Ratulangi. Manado (p = 0,61 > 0,05 with r = 0,06). Keywords: Dietary fat intake, hs-CRP levels, CHD, Obesity. Abstrak: Konsumsi lemak saat ini merupakan hal yang semakin di perhatikan karena perubahan gaya hidup. Lemak yang berlebihan akan meningkatkan obesitas dan menyumbang resiko penyakit jantung. Lemak menghasilkan 9 kkal/gram dengan konsumsi yang dianjurkan sebanyak 20-30% dari total kebutuhan energi. High sensitive-C reactive protein (hs-CRP) merupakan uji yang sangat sensitive untuk mendeteksi resiko kardiovaskular,penyakit jantung koroner (PJK). Tujuan dari penelitian ini ialah untuk mengetahui perbedaan antara asupan lemak dengan kadar hs CRP mahasiswa obes dengan tidak obes pada Fakultas Kedokteran Universitas Sam Ratulangi Manado. Desain penelitian ini bersifat analitik dengan pendekatan cross sectional. Penelitian ini dilakukan pada bulan November-Desember 2012 dengan jumlah sampel sebanyak 59 orang. Hasil penelitian perbedaan asupan lemak obes dan non obes menggunakan uji Mann Whitney dengan nilai p=0,85 >0,05 menunjukan tidak adanya perbedaan asupan lemak mahasiswa obes dengan tidak obes. Nilai p=0,00 < 0,05 menunjukan ada perbedaan kadar hs-CRP mahasiswa obes dan tidak obes. Uji Spearman rank dengan nilai p = 0,61 > 0.05 dengan nilai r = 0,06 menunjukan ada hubungan positif yang lemah tetapi tidak bermakna antara asupan lemak dengan kadar hs-CRP pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi. Kata kunci: Asupan lemak, hs-CRP, PJK, Obesitas.